Analisa Hukum Islam Pada Akad Transaksi Pembulatan Berat Kiriman di PT Tiki Jalur Nugraha Ekakurir Studi Kasus Cabang Utama Sumatera Utara - Fikri Al-Haq Fachryana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
As PT Tiki Strip Nugraha Ekakurir's business grows, there are Islamic legal issues in its business practices that must be straightened out. The issue is the purchase agreement, which is when setting the price of services in this case setting shipping rates based on shipment weight. At present the determination of shipment weight is the existence of a weight rounding system. Therefore there is a need for a study in Islam related to the determination of the weight of consignments in this ijarah contract / transaction. The delivery transaction agreement is an ijarah agreement (service fee), where JNE as a service provider is rewarded (wages) by the service provider (the customer). From the transactions in JNE there are no deviations related to the ijarah contract, because JNE tells the original weight of the scales before rounding. If analyzed from the pillars, terms and some basic legal ijarah then there is no deviation which has been fulfilled in the presence of: 1. Musta jir 2. Ajir (people who are given wages) 3. Shighat 4. Ujrah (wages) 5. Ma qud bih (goods that become objects). The most important requirement in this transaction is that the services provided are halal services. In this pillar that the object must be halal goods, and this depends on each consumer who will send what goods will be sent. Based on the calculation of JNE Main Branch Medan Main Cost component, the additional profit is in a fair condition (because it is less than 20%), meaning that the usury element is not included in the JNE tariff determination.